Pembuatan Game Edukasi BISINDO Pada SLB Negeri Tenggarong Berbasis Android - Catur Indah Handayani; Damar Nurcahyono; Subhan Hartanto (JURNAL VOKASI TEKNIK, 2024)
In East Kalimantan, people with hearing impairments face difficulties in communication and obtaining adequate education, particularly through the use of sign language. The mother tongue used by individuals with hearing impairments is adapted to the visual concepts understood by them and is known as Bahasa Isyarat Indonesia (BISINDO) by the Deaf community across Indonesia. Sekolah Luar Biasa (SLB) teach common sign language. However, state special schools in East Kalimantan are still limited, especially in Kutai Kartanegara Regency, which only has one state special school, SLB Negeri Tenggarong. Therefore, the purpose of this research is to create an Android-based educational sign language game that can be used as an alternative teaching medium for people with hearing impairments at SLB Negeri Tenggarong. Using BISINDO, this game teaches basic vocabulary and conversation sentences in an engaging and interactive way. The game development follows the Serious Game Development (SGD) method, which includes four main production phases: Analysis, Production, Testing, and Release.